Time dependent selfconsistent electron energy distribution functions during nano-second repetitive discharges in reacting N2/H2 mixtures. (18th October 2019) - Colonna, G; Laricchiuta, A; Pietanza, L D
Abstract: Electron energy distribution function, vibrational and electronic excited states are self-consistently solved to investigate the formation of ammonia under nano-second repetitive pulsed discharges. The inclusion of transitions starting from electronically and vibrationally excited states of N2 and H2 molecules in the electron Boltzmann equation is discussed to rationalize the evolution of the electron energy and level distributions, as well as of chemical composition. The results are presented focusing on the dependence of the vibrational distributions of both N2 and H2 molecules and eedf on the applied reduced electric field. The relevance of using complete sets of electron impact cross sections, including transitions from vibrationally excited states has been investigated, comparing with the ground state model.